Experimental and analytical study on dynamic performance of timber floor modules (timber beams). (30th September 2016) - Rijal, Rajendra; Samali, Bijan; Shrestha, Rijun; Crews, Keith
Highlights: Experimental and analytical dynamic investigation of six full-scale timber beams. Performed impact hammer tests on the timber beams with two different spans. The fundamental frequency of all tested beams was above 8 Hz, which is acceptable. Analytical models predicted fundamental frequency of all beams within acceptable range of ±5%. Mean damping ratio of 6 m and 8 m span beams was 0.65% and 0.58%, respectively. Abstract: Timber floors are more susceptible to vibrations and have low impact insulation due to low stiffness and poor damping properties. Recent trends towards long-span and light-weight construction make floor vibration even more critical in satisfying serviceability requirements of floor constructions. This paper presents the results of dynamic tests conducted on timber floor modules (beams) with 6 and 8 m clear spans using an instrumented hammer for floor excitation. Dynamic parameters such as natural frequencies, damping ratios and mode shapes from the tests were evaluated to assess dynamic performance of the beams. The fundamental frequency of the beams was predicted using simple analytical models and good correlation between the test results and predicted values could be obtained.